Hambatan Komunikasi Internal di Organisasi Pemerintahan - Dwi Harivarman (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
The Budget Execution Evaluation and Monitoring Program owned by the Ministry of Finance’s Directorate of Budget Execution has a strategic role in safeguarding the implementation of the Ministry atau Institution budget so that the Indonesian Budget (APBN) can run more optimally. The smoothness of the program depends on the effective communication system at the time of program implementation. This study aims to determine the internal communication barriers in the Directorate of Budget Execution that should be removed for effective communication can occur in the implementation of The Budget Execution Evaluation and Monitoring Program. The research uses descriptive qualitative method with case study, where data is obtained through in-depth interview and observation of informants (officials and staff at Directorate of Budget Execution). The result of the research shows that the internal communication barrier faced by the Directorate of Budget Execution is the difference of perception between the leader and the subordinate about the implementation of the activity, the limited sharing of information practice from the management to the staff, and the leadership style that influences the implementation of the program activity.